The changing architecture of the safety net in insurance worldwide: post crisis developments - Monkiewicz, Jan; Gąsiorkiewicz, Lech; Monkiewicz, Marek (Economics and Business Review, 2015)
This aim of this paper is to explain the safety net of the insurance sectorunderstood as the total means which ensure the safety of the insurance markets and their customers and how it has been heavily affected by recent regulatory initiatives. The paper then provides a review and analysis of the directions of the evolution of the architecture safety net in insurance as compared to banking. Special attention is paid to macroprudential supervision which is believed to constitute a major regulatory innovation in the aftermath of the recent global financial crisis. Additionally new restructuring and resolution concepts and tools are discussed. Particular attention is focused on Global Systemically Important Insurers (G-SII’s) which are the focus of safety net regulation and which provide a regulatory impetus for the remaining part of the industry.